Contained rupture of a large right hepatic artery aneurysm: the ticking bomb within! - Kundil, Byju; Mathews, Mano Zac; Tony, Tina; Kurian, Robin (International Surgery Journal, 2020)
Hepatic artery aneurysms (HAAs) are rare and represents one fifth of visceral aneurysms. We report a case of a 75 year old female who presented to the outpatient department with complaints of abdominal pain and anorexia for 2 weeks. On examination the patient was stable, she had mild tenderness in the right hypochondrial region. Ultrasound abdomen showed an intrahepatic cystic area with both arterial and venous flow, suggesting the possibility of an intrahepatic arteriovenous malformation. Contrast-enhanced computed tomography abdomen showed a large right HAA with contained rupture and intra hepatic extension. She was posted for emergency laparotomy and was found to have a contained rupture a contained rupture of the right HAA of size 10×8 cm with intra hepatic extension. Right hepatectomy was done and the resected margin of liver showed a dilated cystic space with blood clot. Histopathological examination showed intrahepatic aneurysm with atherosclerosis and laminated luminal thrombus. Contained rupture of HAAs with intrahepatic extension are rare. Even though the prevalence of HAAs is low, the risk of rupture is reported to be as high as 20-80% and the mortality following spontaneous rupture is 40%. Hence an aggressive approach to the management of HAA is required whenever detected.